Internalization of the Value of Religious Moderation in Islamic Religious Education Learning at Margokoyo State Elementary School - Slamet Muhamad Susanto; Suwandi Suwandi; Thoha Firdaus (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The purpose of this study is to explain how Islamic Religious Education (PAI) students in grade V at SD Negeri Margokoyo internalize the importance of religious moderation. The significance of teaching religious moderation from a young age in order to develop students who are religious, tolerant, and capable of coexisting peacefully in a pluralistic society is the driving force behind this study. Twenty-five fifth-grade students, Islamic Religious Education instructors, school principals, vice principals for curriculum, and vice principals for student affairs were the research subjects in this descriptive qualitative study. Techniques for gathering data include observation, interviews, and documentation.  Through the phases of data reduction, data presentation, and conclusion drawing, the data was examined utilizing the Miles and Huberman model. Triangulation of sources, methods, and documentation ensures the data's validity. The study's findings demonstrate that the internalization of the value of religious moderation has been successfully accomplished through the support of school administrators, the incorporation of moderation values into curricula and instruction, student coaching, teacher models, and a school culture that promotes harmony and tolerance. Students' educational activities and social interactions incorporate religious moderation values such tawasuth, tawazun, tasamuh, i'tidal, and ta'awun.  The study's conclusions demonstrate that kids exhibit harmonious behavior in the classroom, have a tolerant attitude, are able to respect differences, and collaborate regardless of their religious background. As a result, Islamic Religious Education is crucial in helping children develop moderate, inclusive, and harmonious personalities.